2023
DOI: 10.1001/jamanetworkopen.2023.47700
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Testing in Patients With Unresectable Advanced or Recurrent Non–Small Cell Lung Cancer

Tomohiro Sakamoto,
Taichi Matsubara,
Takayuki Takahama
et al.

Abstract: ImportanceBiomarker testing for driver mutations is essential for selecting appropriate non–small cell lung cancer (NSCLC) treatment but is insufficient.ObjectiveTo investigate the status of biomarker testing and drug therapy for NSCLC in Japan for identifying problems in treatment.Design, Setting, and ParticipantsThe REVEAL cohort study included retrospective data collection and prospective follow-up from 29 institutions across Japan. Of 1500 patients diagnosed with advanced or recurrent NSCLC between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Compared with an earlier period when the first multi-gene panel test, the ODxTT, was introduced into clinical practice in Japan [9,10,15], our results showed that the submission rate and the success rate of multi-gene panel tests have greatly improved. A recent report suggests that a multi-gene panel test performed prior to the initiation of systemic treatment can potentially enhance prognosis by detecting a wider range of driver oncogene alterations than multiple single-gene tests [5], and therefore the improvement in the submission rate and success rate of multi-gene panel tests is expected to contribute to a good prognosis for patients with NSCLC in clinical practice.…”
Section: Discussionmentioning
confidence: 78%
“…Compared with an earlier period when the first multi-gene panel test, the ODxTT, was introduced into clinical practice in Japan [9,10,15], our results showed that the submission rate and the success rate of multi-gene panel tests have greatly improved. A recent report suggests that a multi-gene panel test performed prior to the initiation of systemic treatment can potentially enhance prognosis by detecting a wider range of driver oncogene alterations than multiple single-gene tests [5], and therefore the improvement in the submission rate and success rate of multi-gene panel tests is expected to contribute to a good prognosis for patients with NSCLC in clinical practice.…”
Section: Discussionmentioning
confidence: 78%
“…Notably, BRAF mutations demonstrated a significantly higher frequency in patients with lung cancer with IPF, accounting for 6 of 35 cases (17.1%) [44], which is much higher than the known prevalence of 2-4% in the general lung cancer population [45,46]. As previously mentioned, a retrospective real-world study conducted in Japan [36] revealed that comorbidities, including IP, were associated with the absence of multiplex gene testing. Consequently, NSCLC patients with comorbid IP were not thoroughly investigated for multiple driver gene mutations, considering the underlying risk of drug-induced pneumonia.…”
Section: Driver Gene Mutations In Nsclc With Comorbid Ipmentioning
confidence: 81%
“…Factors associated with the lack of multiplex gene testing were Eastern Cooperative Oncology Group Performance Status of 3 or 4 (odds ratio (OR): 0.47; 95% CI: 0.32-0.70; p < 0.005), comorbidities (OR: 0.54; 95% CI: 0.44-0.67; p < 0.005), and non-adenocarcinoma (OR: 0.70; 95% CI: 0.56-0.87; p < 0.005) in the multivariate model. Among patients with comorbidities, 10.5% had interstitial lung disease [36].…”
Section: Driver Gene Mutations In Nsclc With Comorbid Ipmentioning
confidence: 99%
“…In the Original Investigation titled “Biomarker Testing in Patients With Unresectable Advanced or Recurrent Non–Small Cell Lung Cancer,” 1 published December 15, 2023, the first 2 labels in the x-axis of Figure 1 were inadvertently transposed; the bars indicating multigene testing were inadvertently labeled as single gene testing in the color key of Figure 2; and 2 of the denominators in eTable 3 in Supplement 1 were incorrect (for surgical samples and others in the RNA analysis column). This article has been corrected.…”
mentioning
confidence: 99%